CHARACTER ANALYSIS IN THE MOVIE ALICE THROUGH THE LOOKING GLASS BASED ON PROPP’S THEORY - Marlia, Marlia; Puspasari, Atika; Hikmahyanti, Cita (Jurnal Ilmiah Bina Bahasa, 2017)
Abstract:This research analyzed characters in the movie Alice Through The Looking Glass by using Vladimir Propp?s theory especially in seven spheres of action and thirty-one narrative functions. To conduct this research, the researcher used descriptive method. To analyze the data, the researcher classified the characters into seven spheres of action and classified the sequence into thirty-one narrative functions. The results of this research showed that there were six spheres of action that the researcher found there were villain, donor, helper, princess, dispatcher, and hero and seventeen narrative functions which appeared in the movie Alice Through The Looking Glass which were absentation, mediation, interdiction, beginning counteraction, departure, violation, reconnaissance, provision of magical agent, guidance, unrecognized arrival, transfiguration, villainy, victory, punishment liquidation of lack, return, and wedding.